Adipose Tissue Regeneration: A State of the Art. (3rd October 2012) - Casadei, Alessandro; Epis, Roberta; Ferroni, Letizia; Tocco, Ilaria; Gardin, Chiara; Bressan, Eriberto; Sivolella, Stefano; Vindigni, Vincenzo; Pinton, Paolo; Mucci, Giuseppe; Zavan, Barbara
Abstract : Adipose tissue pathologies and defects have always represented a reconstructive challenge for plastic surgeons. In more recent years, several allogenic and alloplastic materials have been developed and used as fillers for soft tissue defects. However, their clinical use has been limited by further documented complications, such as foreign-body reactions potentially affecting function, degradation over time, and the risk for immunogenicity. Tissue-engineering strategies are thus being investigated to develop methods for generating adipose tissue. This paper will discuss the current state of the art in adipose tissue engineering techniques, exploring the biomaterials used, stem cells application, culture strategies, and current regulatory framework that are in use are here described and discussed.